Implementing the European Quality Assurance in Vocational Education and Training (EQAVET) at National Level: Some Insights from the PEN Leonardo Project - Gatt, Suzanne; Faurschou, Kim (International Journal for Research in Vocational Education and Training, 2016)
EQAVET, the quality assurance tool in vocational and educational training, was developed in response to the need for a supply of a trained workforce for labour market needs. Implementation of EQAVET at national level, however, remains a challenge. The research reported here focused on the implementation of QA processes by VET providers in 4 countries: Malta, Italy, Turkey, and Sweden. Data was collected through a questionnaire with 62 VET providers. Responses showed that there is an overall commitment to quality. There is, however, little knowledge of EQAVET across the countries, with the exception of Malta. None the less, all VET providers have implemented some aspects of EQAVET, even if not always intentionally. The situation is, however, far from EQAVET being fully implemented. Reflections are made on whether the EQAVET model specifically or qualification assurance principles assurances should be promoted across Europe.